2021
DOI: 10.1038/s41585-021-00450-8
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of microbiome studies for urolithiasis: an international consensus agreement

Abstract: Numerous metagenome-wide association studies (MWAS) for urolithiasis have been published, leading to the discovery of potential interactions between the microbiome and urolithiasis. However, questions remain about the reproducibility, applicability and physiological relevance of these data owing to discrepancies in experimental technique and a lack of standardization in the field. One barrier to interpreting MWAS is that experimental biases can be introduced at every step of the experimental pipeline, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 68 publications
3
30
0
Order By: Relevance
“…Consistent with their reports, we found that E. coli also accounted for a greater proportion of the microbiomes in nephrolithiasis patients than in healthy individuals. Additionally, previous studies have determined that the genus Staphylococcus was overrepresented, while Lactobacillus was less abundant in nephrolithiasis patients than in healthy controls (Zampini et al, 2019;Liu et al, 2020a;Kachroo et al, 2021); again, our findings support these reports. It has been shown that Staphylococcus promotes the formation of kidney stones by producing the enzyme urease, which increases pH, while Lactobacilli exerts an inhibitory action by degrading oxalate (Lewanika et al, 2007;Torzewska et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with their reports, we found that E. coli also accounted for a greater proportion of the microbiomes in nephrolithiasis patients than in healthy individuals. Additionally, previous studies have determined that the genus Staphylococcus was overrepresented, while Lactobacillus was less abundant in nephrolithiasis patients than in healthy controls (Zampini et al, 2019;Liu et al, 2020a;Kachroo et al, 2021); again, our findings support these reports. It has been shown that Staphylococcus promotes the formation of kidney stones by producing the enzyme urease, which increases pH, while Lactobacilli exerts an inhibitory action by degrading oxalate (Lewanika et al, 2007;Torzewska et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Samples were immediately frozen in liquid nitrogen, and subsequently stored under – 80 ℃. The whole process maintained sterility via the instruction of MICROCOSM (an international consortium for microbiome in urinary stone disease) [ 15 ]. After stone composition analysis, we selected urine samples of patients with a definite diagnosis of CaOx stones and applied 16S rRNA gene sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, metadata does not only refer to sample attributes, but also to sample preparation and processing [128]. The variability of metadata can limit the conclusions, since the observed patterns might not be attributable to a certain factor(s) [129,130] that should also be considered when selecting study subjects. In this context, we call attention to the necessity of validating metadata submitted to public repositories by providing immediate and informative feedback to the submitting researchers [128].…”
Section: Data Issues and Potential Solutionsmentioning
confidence: 99%